PENGARUH PENERAPAN SISTEM CPNS ONLINE TERHADAP KEPUASAN MASYARAKAT MENGGUNAKAN METODE TAM - Siti Nurdiani; Rizky Ade Safitri; Dwiza Riana (Jurnal Techno Nusa Mandiri, 2019)
Information systems are a combination of information technology and activities of people who use that technology to support operations and management. Currently, the procurement of Prospective Civil Servants (CPNS) has implemented system technology in carrying out each activity. One form of implementation is in the form of an online CPNS system. The purpose of this study is to find out what are the effects of system quality, information quality, online CPNS service quality on community satisfaction following online CPNS. The method used is TAM (Technology Acceptance Model) with variable system quality, information quality, and service quality. Based on the results of the study of the effect of applying the online CPNS system to community satisfaction, the results showed that: There is a significant influence between the system quality variables on community satisfaction, there is no significant effect between the quality of information on community satisfaction. There is a significant influence between service quality variables on community satisfaction.